Kedudukan Penyidik Pegawai Negeri Sipil (PPNS) dalam Sistem Peradilan Pidana Pasca Pembaruan Kuhap UU Nomor 20 Tahun 2025 - Tri Wahyu Pranoto; Tuti Elawati; Muhammad Panca Prana Mustaqim Sinaga; Zahra Malinda Putri (JUSTLAW : Journal Science and Theory of law, 2025)
The reform of the Indonesian Criminal Procedure Code (Kitab Undang-Undang Hukum Acara Pidana/KUHAP) has implications for the reconfiguration of investigative authority within the criminal justice system, including the position of Civil Servant Investigators (Penyidik Pegawai Negeri Sipil/PPNS). Normatively, PPNS investigative authority is conferred attributively by sectoral legislation. However, the post-renewal KUHAP continues to place the exercise of PPNS investigative authority within a framework of coordination and supervision by police investigators that has not been formulated in a limiting and clear manner. This condition gives rise to juridical issues concerning the clarity of PPNS’s position and the boundaries of its authority within the integrated criminal justice system. This study aims to analyze the position of PPNS following the renewal of the KUHAP and its implications for the principles of legal certainty and functional differentiation among law enforcement authorities. The research employs normative legal research using statutory and conceptual approaches. The findings indicate that the renewed KUHAP has not yet fully provided normative clarity in structuring investigative authority, as the existing regulatory construction does not offer adequate normative guarantees for the realization of a functional and equal configuration of investigative authority for PPNS. Therefore, it is necessary to reinforce regulatory provisions within the KUHAP that place PPNS as a subsystem of investigation with functional autonomy, within the limits of attributive authority granted by sectoral legislation, in order to ensure legal certainty and the effectiveness of criminal law enforcement.